Democratic backsliding in sub-Saharan Africa and the role of China's development assistance. Issue 4 (2nd October 2019) - Hess, Steve; Aidoo, Richard
ABSTRACT: The article observes 19 hybrid regimes in sub-Saharan from 2005 to 2014 and examines the influence of each country's level of economic development, short-term macroeconomic performance, and ratio of Chinese to Western official financing on the trajectory of its political development, with some regimes making improvements in the quality of democratic governance, others backsliding into greater authoritarianism, and still others remaining largely stable. The study suggests that while Western leverage might have been influential in the democratic development of observed hybrid regimes, it could have been counterbalanced by the presence of alternative Chinese foreign assistance.